Altered cardiovascular adaptability in depressed patients without heart disease - Ehrenthal, Johannes C.; Herrmann-Lingen, Christoph; Fey, Marco; Schauenburg, Henning (The world journal of biological psychiatry, 2010)
Objectives. Despite its clinical importance and relevance for health care policy, the pathways between depression and stress regulation remain poorly understood. The objective of our study was to compare cardiovascular and autonomic responses to brief psychosocial stress in a group of severely depressed subjects without heart disease and a non-depressed control-group. Methods. We recorded cardiovascular and autonomic reactions to two different stress tasks including anger recall and mental arithmetic in a sample of 25 severely depressed and 25 non-depressed subjects. Aggregated data were compared with repeated-measures MANOVA. We used contrasts to evaluate different response patterns concerning cardiovascular and autonomic reactivity vs. recovery. Results. Depressed subjects showed overall reduced high-frequency heart rate variability and an altered cardiovascular adaptability concerning heart rate, blood pressure, cardiac output, and, on a trend level, peripheral resistance. With few exceptions, we found no differences between reactivity vs. recovery response patterns. Conclusions. Our results provide further evidence for altered cardiovascular reactivity and impaired cardiac autonomic functioning in depression. Further research is needed on psychophysiological response to either more disease-oriented or more personality-oriented stressors.